Examining Readers' Critical Literature Circle Discussions of Looking for Alaska. Issue 2 (18th June 2021) - Chisholm, James S.; Cook, Mike P.
Abstract: Promising approaches to transforming English language arts classrooms into dialogic, democratic, and critical spaces for literature discussions involve the selection of compelling young adult literature (YAL) and the use of student‐centered discussion strategies (e.g., literature circles). Scholars have demonstrated, however, the shortcomings of YAL and literature circles for interrogating sociopolitical content in literary texts and society. Drawing on a framework for critical literature circle roles, the authors examined how 23 undergraduate readers leveraged these roles to engage in critical conversations as they discussed John Green's YA novel, Looking for Alaska . A qualitative, inductive analysis of discussion transcripts revealed how participants interrogated the text and society, especially in relation to gender stereotypes, and identified but also enacted stereotypes about culture and youth. Implications call for explicit support for readers in trying on critical literature circle roles and engaging in dialogic interactions that promote critical consciousness with YAL.